Adam Mosseri: Constructing Instagram's Top Dad - Leaver, Tama (2022)
Using a detailed content analysis of his public commentary, public social media posts, and captured ephemeral social media, this paper argues that Head of Instagram Adam Mosseri has strategically constructed a public persona as an active, engaged and concerned parent. While this parenting persona emerges from a relatively typical combination of professional and personal/parenting content, I argue this persona has been strategically developed to be leveraged as Meta pursues ‘Instagram Kids’ or other apps aimed at under13s which ostensibly empower parents as initial moderators of the children’s online experiences but are simultaneously rich sources of children’s personal data and activity, something of great monetizable value to Instagram and parent company, Meta.